ESTABLISHMENT OF CAREER SELF EFFICACY CAPABILITIES THROUGH GROUP GUIDANCE WITH PROBLEM-SOLVING TECHNIQUES - Akhmad Abdul Hakim; Agus Supriyanto; Bambang Suprihatin; Nurlita Hendiani (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2022)
Career confidence needs to be developed through career guidance services by school counsellors. Not all individuals have confidence in their career, although various studies have tested it effectively. This study focuses on increasing self-efficacy through group guidance services with problem-solving techniques expected to increase students' self-efficacy to achieve optimal career development. This research is qualitative research with literature study with data collection techniques are journals, articles and books from 2014-to 2022 to find the concept of implementing career self-efficacy formation through problem-solving techniques with group guidance services. The data analysis technique was analysed descriptively qualitatively through the stages of data reduction from various relevant writings. Low self-efficacy is a belief with the characteristics of being slow in fixing or regaining self-efficacy when faced with failure, unsure of being able to meet the problem, avoiding complex problems, reducing effort, quickly giving up when facing difficulties and doubting one's abilities. Problem-solving needs to be implemented in group guidance services to develop career self-efficacy. Counsellors must be able to implement problem-solving techniques in group guidance services to develop career self-efficacy.